Profiling the rapist: case study of rapists in the Seremban, Johor Bahru, Kajang and Sungai Buloh prisons / Rachel Samuel, Prof. Madya Dr. Rohana Ariffin and Sujatha Menon - Samuel, Rachel; Ariffin, Rohana (Prof. Madya Dr.); Menon, Sujatha (Institute of Research, Development and Commercialization, 2004)
The number of rape incidents in the country is showing an increasing trend. It is reported that an average of four women get raped everyday in Malaysia. As the rapists are the perpetrators of the crime, it is hoped that an insight into their thoughts, feelings, perception and attitude would help reduce the number of rape incidents in our country. The objectives of the study include obtaining a socio-economic profile of the rapists, understanding the family background of the rapists and outlining programmes which can help combat the rise of rape incidences. Through the data obtained, the study intends to outline the profile of a Malaysian rapist. A total of 90 convicted rapists from the above mentioned prisons were interviewed. Majority of the offenders were Malay and were aged between 45 to 55 years old. Our study showed that the most common types of rape were incest and acquaintance rape. The victims were mainly 16 years and below. The Malaysian rapist originates mainly from the rural areas and has low education levels. They are mainly married. In terms of relationship, most of them reported good relationship with their mothers but not their fathers. Their views concerning females in general were degrading and humiliating. These views affected their overall perception and attitudes towards women. Though rape is a violent crime, the responses from the convicted rapists show that they see rape as sex.